Courtesy and Civic Virtue as Determinants of Organizational Citizenship Behavior in Bureaucratic Human Resource Management: A Study of the Kotamobagu Governmen - Mokoginta, Sahaya Subagio (KnE Social Sciences, 2025)
Human resource (HR) capabilities are needed to achieve the effectiveness of public sector services. So, it is necessary to develop agile HR management starting from employee planning, competency improvement, career development, and welfare improvement. This is so that competent, productive, and high integrity human resources can be achieved. This research aims to see how aspects of courtesy and civic virtue in the development of bureaucratic HR management in the Kotamobagu Government can be maximally implemented. It uses a qualitative approach, and data were collected through observation, in-depth interviews, and documentation. Data sources consisted of primary and secondary data, while data analysis was conducted using interactive methods. The informants in this research are stakeholders and other parties directly involved in the implementation of bureaucratic HR management development in Kotamobagu Government. The results show that the development of organizational management in Kotamobagu has begun to build a strong social foundation to support openness and mutual respect. This is implemented with active participation, appreciation of contributions, and leaders who open space for dialogue. However, the reality is that there are still work culture issues, such as leaders who maintain an authoritarian style and make decisions unilaterally without involving their staff. This limits the space for employees to openly express new ideas. Other problems such as passivity and lack of knowledge of government staff are also obstacles to increasing openness to implement bureaucratic HR management.